Fresh and mechanical properties of concrete containing recycled fine aggregate as partial sand replacement - Nur Farah Aziera, Jamaludin; Lau, Loong Jie; Khairunisa, Muthusamy; Hanis Nadiah, Ruslan; Nabilla, Mohamad (Elsevier Ltd, 2023)
Concrete is one of the world's oldest established construction materials, having been employed in the creation of various structures throughout history. Due to increased demand, the materials used in concrete buildings, particularly granite aggregates and natural sand, are rapidly decreasing. Continuous use of these natural resources has a detrimental effect on the ecosystem. Simultaneously, concrete waste from construction and demolition waste (CDW) created landfills and environmental damage. Therefore, recycled fine aggregate (RFA) was utilized in this research to replace natural sand. This experiment used a total of five mixtures. Mixes with RFA replacement amounts of 0%, 10%, 20%, 30%, and 40% were cast and subjected to water curing. The slump test, compressive test, and water absorption test were done for concrete containing various percentages of RFA. Incorporation of RFA up to 20% enhances the concrete strength. Generally, concrete produced using RFA up to 40% exhibits water absorption not exceeding 10% enabling it to be categorized as good quality concrete. The approach of channeling concrete waste to be utilized as recycled fine aggregate would decrease waste dumping at landfill and mining of sand from local rivers.